تطبيق المعارف المكتسبة للطالب الجامعي في تطوير التواجد الرقمي للجامعة. دراسة حالة: الإعلان الممول لصفحة مخبر(lezinru)، بجامعة برج بوعريريج. - سراي, أم السعد; بن ثامر, كلتوم (جامعة الوادي - University of Eloued, 2021)
نهدف من خلال هذه الورقة البحثية إلى الكشف عن أهمية استثمار الجامعة لمعارف طلابها بتطبيق معارفهم المكتسبة من خلال المناهج الدراسية وخاصة (التسويق الالكتروني)، في تعزيز تواجدها الرقمي وذلك من خلال فتح المجال للطلبة بالتسويق لاسم الجامعة من خلال تناول فضاء الجامعة ومكوناته كدراسة حالة تطبيقية، حيث تم تصميم إعلان ممول على الفيسبوك يستهدف جمهور من أساتذة جامعين من مصر، وتم تسجيل تفاعل قدر بـ 3300 شخص. Through this research paper, we aim to reveal the importance of the university's investment of its students ’knowledge by applying the knowledge acquired, through the curriculum, especially (e-marketing), in enhancing its digital presence by opening the field of marketing to the brand of the university, where a facebook funded ad was designed to target an audience of university professors from Egypt, where an estimated interaction of 3300 people was recorded.
The reality of applying the acquired knowledge to the university student in developing the university's digital presence Case study: The funded announcement of the page of the Laboratory )LEZINRU( at the University of Bordj Bou Arreridj
مقال
Keywords: الجامعة، الطالب الجامعي، التواجد الرقمي، مخبر (LEZINRU).